Numerical Analysis on the Storage of Nuclear Waste in Gas-Saturated Deep Coal Seam. (12th July 2021) - Teng, Teng; Wang, Yuming; Zhu, Xiaoyan; Zhang, Xiangyang; Yi, Sihai; Fan, Guowei; Liu, Bin
Abstract : Nuclear power has contributed humanity a lot since its successful usage in electricity power generation. According to the global statistics, nuclear power accounts for 16% of the total electricity generation in 2020. However, the rapid development of nuclear power also brings up some problems, in which the storage of nuclear waste is the thorny one. This work carries out a series of modeling and simulation analysis on the geological storage of nuclear waste in a gas-saturated deep coal seam. As the first step, a coupled heat-solid-gas model with three constitutional fields of heat transfer, coal deformation, and gas seepage that based on three governing conservation equations is proposed. The approved mechanical model covers series of interactive influences among temperature change, dual permeability of coal, thermal stress, and gas sorption. As the second step, a finite element numerical model and numerical simulation are developed to analyze the storage of nuclear waste in a gas-saturated deep coal seam based on the partial differential equations (PDE) solver of COMSOL Multiphysics with MATLAB. The numerical simulation is implemented and solved then to draw the following conclusions as the nuclear waste chamber heats up the surrounding coal seam firstly in the initial storage stage of 400 years and then be heated by the far-field reservoir. The initial velocity of gas flow decreases gradually with the increment of distance from the storage chamber. Coal gas flows outward from the central storage chamber to the outer area in the first 100 years when the gas pressure in the region nearby the central storage chamber is higher than that in the far region and flows back then while the temperature in the outer region is higher. The modeling and simulation studies are expected to provide a deep understanding on the geological storage of nuclear waste.